ANALYSIS OF THE APPLICATION OF GOVERNMENT ACCOUNTING STANDARDS ON DEPARTMENT OF FORESTRY IN EAST JAVA PROVINCE - Erina Sudaryati; Toto Da'i Permana (Universitas Airlangga, 2020)
The purpose of this study is to understand and analyze the application of accrual-based Government Accounting Standards in aspects of Financial Statements, Human Resources, and Information Technology. Data collection techniques were carried out by interviews and documentary studies with the leadership and employees of the finance sub-section of the East Java Provincial Forestry Service. The results showed that the Forestry Service of East Java Province began to apply the Accrual-Based Accounting Standards for the 2015 fiscal year. The obstacles faced were the lack of time preparation, frequent application errors, and some staff experiencing difficulties. In the 2016-2017 period the development and development of Government Accounting Standards related to HR Accruals has been carried out intensely.